The role of cytokines in the pathogenesis of infectious complications in surgical treatment of obstructive jaundice of gallstone origin - O. V. Smirnova; N. G. Elmanova (Бюллетень сибирской медицины, 2021)
Aim. To study the content of cytokines in the blood serum of patients with obstructive jaundice of gallstone origin before and after surgical treatment, depending on the development of postoperative complications.Materials and methods. The treatment group consisted of 70 patients with the diagnosis of obstructive jaundice of gallstone origin, verified following a comprehensive clinical and instrumental examination. In 54 patients, the postoperative period was uncomplicated, and in 16 patients, various infectious complications in the postoperative period were revealed. The control group consisted of 125 healthy volunteers. The concentration of six cytokines (interleukin (IL)-2, IL-4, IL-18, IL-10, tumor necrosis factor alpha (TNFα), and interferon gamma (INF γ)) was determined using reagent kits manufactured by Vector-Best LLC (Novosibirsk, Russian Federation) by enzyme-linked immunosorbent assay on the Thermo Scientific analyzer (BioMerieux, France).Results. We identified significantly high concentrations of proinflammatory cytokines in the blood serum of patients with obstructive jaundice of gallstone origin upon admission, compared with the data obtained in the study of blood serum in the control group and in patients with obstructive jaundice after surgery. In the postoperative period in patients with obstructive jaundice without complications, the proinflammatory cytokines are significantly reduced and IL-4 is increased, whereas with the development of infectious complications, the level of proinflammatory cytokines is significantly elevated.Conclusion. In the pathogenesis of obstructive jaundice, a local inflammatory process plays an essential role. This is confirmed by statistically significant changes in the studied cytokines. The established increase in the concentration of IL-4, which has anti-inflammatory activity, indicates its importance in the mechanisms underlying the absence of infectious complications in the postoperative period of obstructive jaundice of gallstone origin. The revealed increase in the levels of IL-18, TNFα, and INFγ in the blood serum of patients suggests their role in the pathogenesis of infectious complications in the postoperative period of obstructive jaundice of gallstone origin.